Constructing moderate attitude through religious education - Sihombing, Adison Adrianus; Maigahoaku, Fredrikus Djelahu (Jurnal Cakrawala Pendidikan, 2025)
The social phenomenon of the last decade, often characterized by extreme-radical behavior,demonstrates the significance of moderation. Moderate attitudes are essential to ensure harmony in a multi-religious society, such as Indonesia. This study aims to examine the role of religious education in fostering students' moderate attitudes. It is a qualitative study based on both primary and secondary data. The primary data were obtained through questionnaires and interviews with high school students from six religions: Islam, Catholicism, Protestantism, Hinduism, Buddhism, and Confucianism across Jakarta, Tangerang, Depok, and Labuan Bajo. The secondary data were collected from online news sources and previous studies. The study was conducted from May to July 2022. The findings suggested that from the perspective of students, religious education promotes moderate attitudes by enabling them to respect differences and live in harmony. This can be achieved through three essential pillars of religious education: quality textbooks, moderate teachers, and conducive school atmosphere. Therefore, religious education is a determining element in cultivating moderate behavior that helps sustain harmony within a pluralistic society.